Developing a theory of change for a community‐based response to illegal wildlife trade. Issue 1 (4th November 2016) - Biggs, Duan; Cooney, Rosie; Roe, Dilys; Dublin, Holly T.; Allan, James R.; Challender, Dan W.S.; Skinner, Diane
Abstract: The escalating illegal wildlife trade (IWT) is one of the most high‐profile conservation challenges today. The crisis has attracted over US350 million in donor and government funding in recent years, primarily directed at increased enforcement. There is growing recognition among practitioners and policy makers of the need to engage rural communities that neighbor or live with wildlife as key partners in tackling IWT. However, a framework to guide such community engagement is lacking. We developed a theory of change (ToC) to guide policy makers, donors, and practitioners in partnering with communities to combat IWT. We identified 4 pathways for community‐level actions: strengthen disincentives for illegal behavior, increase incentives for wildlife stewardship, decrease costs of living with wildlife, and support livelihoods that are not related to wildlife. To succeed the pathways, all require strengthening of enabling conditions, including capacity building, and of governance. Our ToC serves to guide actions to tackle IWT and to inform the evaluation of policies. Moreover, it can be used to foster dialogue among IWT stakeholders, from local communities to governments and international donors, to develop a more effective, holistic, and sustainable community‐based response to the IWT crisis.